2020
DOI: 10.3390/ijerph17030727
|View full text |Cite
|
Sign up to set email alerts
|

Job Burnout Among Primary Healthcare Workers in Rural China: A Multilevel Analysis

Abstract: The health workers in rural primary care systems are at the increasing risk of job burnout. To explore the prevalence and associated factors of the job burnout among the primary healthcare worker in rural China, a cross-sectional survey was conducted among 15,627 participants in 459 township hospitals from six provinces. A combination of stratified multi-stage sampling and cluster sampling method, and a self-administrated questionnaire with the Chinese version of the Maslach Burnout Inventory-General Scale (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 44 publications
4
54
2
Order By: Relevance
“…Overall, serious job burnout of rural PHC workers in China still exists. These findings are similar with the conclusions reported in previous studies about the burnout symptom of PHC workers [8]. With the implementation of the national health coverage strategy, the workload of PHC workers in China is gradually increasing.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, serious job burnout of rural PHC workers in China still exists. These findings are similar with the conclusions reported in previous studies about the burnout symptom of PHC workers [8]. With the implementation of the national health coverage strategy, the workload of PHC workers in China is gradually increasing.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, job burnout of different professional PHC workers vary. Xu reported that doctors had higher level of burnout than nurses, pharmacists, and other technicians of the PHC network [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Moreover, the relocated RHWs have to commute a certain distance daily, in addition to the field travel that they have to do as part of their usual work, often without adequate transportation facilities, which may lead to burnout. 56 According to previous studies, 30-40% of healthcare workers may suffer from burnout. [57][58][59] The topic of depression is fairly broad.…”
Section: Discussionmentioning
confidence: 99%
“…Job burnout was assessed with the Maslach Burnout Inventory-General Scale (MBI-GS). 36 The Chinese version of MBI-GS composed of 15 items, which is widely used among the Chinese population, 37,38 and it has three dimensions: emotional exhaustion (5 items, such as, "I feel used up at the end of the workday"), depersonalization (4 items, such as, "I have become less enthusiastic about my work"), and personal accomplishment (6 items, such as, "I deal very effectively with the problems of my work"). There are seven selected answers for each item: never, rarely (several times per year), sometimes (once a month), often (several times per month), frequently (once a week), always (several times per week) and every day.…”
Section: Job Burnoutmentioning
confidence: 99%